The Law Enforcement Against the Criminal Acts of Destruction of Crops - Eddy Rifai (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
This research uses a normative juridical approach to study the law enforcement against the criminal acts of destruction of crops, about the regulation on the Civil and Agrarian Law. The research approach uses a normative juridical approach that is based on legislation, theories, and concepts related to writing research. The result of the research asserts that the law enforcement against the criminal acts of destruction of crops based on the judges of the Supreme Court Decision No. 1909 K / Pid / 2010, using the viewpoint of Agrarian Law to the principle of horizontal separation asset that the holders of rights to land only control the extent of its surface, while the building or anything inherent in the land have different ownership rights to its land. The criminal law enforcement using viewpoint of Law No. 5 Of 1960 Regarding The Basic Regulations On Agrarian Principles (UUPA) did not need to prove the ownership of the land between the two conflicting party but to prove who the owner of the destroyed crops is. If the plant grows the property of the complainant party then the reported person will meet the elements as perpetrators of criminal acts in the Article 406 paragraph (1) of the Criminal Code. However, by using the legal basis of the Law Number 51 PRP of 1960 on Prohibition to Using the Land without Obtaining the Permission from the Owner of the Land or the Authorized Person (the “Law No 51 PRP/1960”), landowners can maintain proprietary rights and submit the case to the legal process procedure, hence it does not need to happen that the crop destruction by the owner of the land will be entangled in criminal law pursuant to the Article 406 paragraph (1) Criminal Code. Keyword: Law Enforcement, The Criminal Acts, The Destruction of Crops.